2009
DOI: 10.1007/s12648-009-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Fe doped NiO

Abstract: : Mott-Hubbard anti-ferromagnetic insulator, NiO shows p-type semiconducting behaviour due to vacancy at Ni 2+ site in its bunsenite structure. We report the modification of structural and magnetic order in NiO on Fe doping. NiO samples at different Fe concentrations in the range 0 to 5 at.% have been prepared by chemical co-precipitation and post thermal decomposition method. Both structural and magnetic characterization reveal that with increasing Fe doping concentration, NiO evolves as a magnetically inhomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 20 publications
2
26
2
Order By: Relevance
“…Based on this fact, much effort has been put forth to determine ways to utilize visible light in this photocatalytic system. The simplest successful approaches have been to modify the TiO 2 nanostructures itself to enhance its response to visible light via doping, depositing, loading of TiO 2 nanostructures and other methods [26][27][28][29][30][31][32][33][34][35][36][37]. A comparison of the photocatalytic activity of the present study with similar studies is presented in Table 4.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on this fact, much effort has been put forth to determine ways to utilize visible light in this photocatalytic system. The simplest successful approaches have been to modify the TiO 2 nanostructures itself to enhance its response to visible light via doping, depositing, loading of TiO 2 nanostructures and other methods [26][27][28][29][30][31][32][33][34][35][36][37]. A comparison of the photocatalytic activity of the present study with similar studies is presented in Table 4.…”
Section: Resultsmentioning
confidence: 96%
“…Mallick et al investigated properties of Fe doped NiO. Their studies showed that the strain increases with increasing Fe content and attains a maximum value for 3 at.% Fe in NiO [30]. Forghani et al [31] studied strain and defects in Si-doped (Al)GaN epitaxial layers and showed that Si induces tensile strain in (Al)GaN films.…”
Section: Resultsmentioning
confidence: 99%
“…The functionalization of CNTs is commonly performed using the chemical oxidation process introducing functional groups such as -COOH, C-O, C=O, and -OH on the surface of CNTs; such groups act as active surface sites for metal attachment [20,21]. NiO nanostructure can be synthesized through various methods such as co-precipitation [22], sol gel [23], hydrothermal [24], spray pyrolysis method [25], and chemical precipitation [26]. In this study, NiO/CNT nanocomposite was synthesized by chemical precipitation method, which was simple and cost efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been adopted for the synthesis of NiO nanostructures such as sol-gel, 10,11 co-precipitation, 12 hydrothermal, 13 solvo-thermal 14 and chemical precipitation. 15 In the present study, NiO nanocubes have been synthesized using the chemical precipitation route, which is simple and low cost.…”
Section: Introductionmentioning
confidence: 99%